Self-concept, material influence and views on parenting of male adolescents with fathers working abroad in selected high schools in Anini-y, Antique. - Gidaya, Kristoffer Ryan T.
This is a descriptive study sought to find out and describe the self-concept, amternal influence and views on parenting of male adolescents with fathers working abroad in selected high schools in Anini-y, Antique. Forty-two (42) male adolescents with fathers working abroad from St. Therese's High School (26) and St. Andrew's High School (16) aging 13-16 years old were purposely chosen to serve as respondents., Three instruments were utilized for this study, namely,: Self Description Questionnaire II, Maternal Influence Scale and Views on Parenting Scale. Results showed that male adolescents with fathers working abroad in selected high schools in Anini-y, Antique registered a positive self-concept. It was also found out that the respondents have a high degree of maternal influence because of theri prolong attachment with their mothers. This is also a form of compensation of mothers to the absence of their fathers. In terms of views on parenting, the respondents have positive views towards parenting wherein they value the nurturing behavior of a parent.